2019
DOI: 10.2174/0929866526666190911144057
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Effect of Tilapia Fish (Oreochromis niloticus) Lectin on BALB/c Mice Splenocytes

Abstract: Background: Lectins have been studied in recent years due to their immunomodulatory activities. Objective: We purified a lectin named OniL from tilapia fish (Oreochromis niloticus) and here we analyzed the cell proliferation and cytokine production in Balb/c mice splenocytes. Methods: Cells were stimulated in vitro in 24, 48, 72 hours and 6 days with different concentrations of OniL and Con A. Evaluation of cell proliferation was performed through [3H]-thymidine incorporation, cytokines were investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous studies showed that mannose-binding lectins as Lens culinaris (lentil) lectin (LcL) and Narcissus pseudonarcissus (daffodil) lectin (NpL), a α-d-mannose-binding protein, did not elicit potent cytotoxicity against osteosarcoma cells [ 56 ]. Furthermore, a study by da Silva et al [ 57 ] showed that OniL was able to favor the proliferation of Balb/c splenocytes without causing significant cytotoxicity to these cells. Furthermore, our fluorescence microscopy assay showed that the cells remained adhered to the surface of TiO 2 NTs, presenting a preserved morphology and nuclei integrity throughout the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that mannose-binding lectins as Lens culinaris (lentil) lectin (LcL) and Narcissus pseudonarcissus (daffodil) lectin (NpL), a α-d-mannose-binding protein, did not elicit potent cytotoxicity against osteosarcoma cells [ 56 ]. Furthermore, a study by da Silva et al [ 57 ] showed that OniL was able to favor the proliferation of Balb/c splenocytes without causing significant cytotoxicity to these cells. Furthermore, our fluorescence microscopy assay showed that the cells remained adhered to the surface of TiO 2 NTs, presenting a preserved morphology and nuclei integrity throughout the experiments.…”
Section: Resultsmentioning
confidence: 99%